Territorial tax system reform and multinationals' foreign cash holdings: New evidence from Japan - Xing, Jing (Journal of Corporate Finance, 2018)
Using matched affiliate-parent data, we investigate whether Japan's move from the worldwide tax system to the territorial tax system in 2009 affects cash holdings of Japanese overseas affiliates. We find that Japanese overseas affiliates facing high tax costs of repatriation under the worldwide tax system reduce cash holdings after the reform. Affiliates also deplete cash holdings after the reform if their parent companies rely on costly external financing or face strong domestic sales growth. The reform does not have a greater impact on affiliates with more pre-reform cash reserves. Our study provides new evidence for the impact of taxation on multinational companies' foreign cash holdings.